Implementación en 3 niveles de harina de cacao (Teobroma cacao) 5; 10 y 15% sustituyendo la proteína en dietas de pollos de engorde. - Jumbo Martínez, Milton Gilberto (2021)
The objective of this research project is to look for new alternatives in diets for broilers in production using low-budget raw materials or wastes such as cocoa husks, these diets seek to replace a percentage of protein which influences the growth and weight gain of the animals. Therefore, different percentages of cocoa meal have been evaluated, corresponding to; T1 (5% in addition), T2 (10% in addition) and T3 (15% in addition), in order to establish if there are better results compared with a control treatment, T0 (Base), establishing in the study 4 treatments of 25 birds with their respective repetitions which will help to evaluate and control the different variables. The first step of the project was the characterization of the cocoa meal extracted from the cocoa husk, in order to determine its nutritional values for the study. The purpose of the study was to know the variables in a poultry production such as weight gain, feed consumption, feed conversion and nutritional quality of the meat, these data were collected during the project period, with an estimated time of 42 days, in order to demonstrate feed efficiency in the study treatments. For this purpose, the data were analyzed in a Bonferroni Tes, determining positive results in the T1 treatment (5%), in the growth phase, however, in the finishing phase it loses weight gain, so it is recommended to carry out more studies in low percentages to determine its productive variables.